Poster 182: Beach Chair vs Lateral Decubitus Surgical Positioning for Arthroscopic Anterior Shoulder Stabilization: A Retrospective Comparison of Clinical and Patient-Reported Outcomes. Issue 7 (30th July 2022) - Streicher, Sydney; Osman, Alim; Zareef, Usman; Ukekwe, Chukwuka; Freedman, Kevin; Erickson, Brandon; Hammoud, Sommer; Bishop, Meghan; Paul, Ryan
Objectives: Surgical positioning can affect intra- and post-operative complication rates for many reasons, including potential differences in anatomic approaches and proximity to nearby nerves. The beach chair and lateral decubitus positions are the two most common positions for shoulder arthroscopy, and each offers their own unique advantages and disadvantages for surgeons. Beach chair allows for an easier transition to open surgery if necessary, and also has a lower incidence rate of neuropathies, relative to lateral decubitus. However, the lateral decubitus positioning allows for better access to the glenohumeral joint, easier visualization of the labrum, and greater circumferential access to the joint. The surgical position is often selected according to each individual surgeon's preference, with no clear superiority of one position over the other. This study was conducted to compare clinical and patient-reported outcomes between patients who underwent arthroscopic anterior shoulder stabilization in beach chair vs. lateral decubitus positions. Methods: A list of all patients diagnosed with the CPT codes 29806 and 29807 from 2015-2019 was obtained from the medical records. Patients were only included if anterior instability was confirmed, arthroscopic surgery was performed in response to shoulder instability, and a minimum of 2-year follow-up was available. Data collected for eligible patients includes: pathology present (Hill-Sachs lesion, bony Bankart lesion), number and location of anchors used, surgery duration, intra-operative and post-operative complications, recurrent instability, reoperation, and revision. Patients were also contacted to complete patient-reported outcome surveys including the American Shoulder and Elbow Surgeons (ASES) score, Oxford Shoulder Score, Single Assessment Numeric Evaluation (SANE), and a return to sport (RTS) questionnaire. Demographic, intra-operative data, and post-operative outcomes were compared between patients who underwent surgery in beach chair vs lateral decubitus positioning. Results: 294 patients were included in this study, 162 patients who underwent surgery in the lateral decubitus position and 132 in beach chair position with an average follow-up of 3.3 years. There were no significant differences in demographics, concomitant surgeries, prevalence of Hill-Sachs and bony Bankart lesions, surgery duration, or intra-operative complications between groups (all p>0.05). Beach chair was associated with an increased number of anchors used (4.0 vs. 3.3, p=0.01) and a smaller proportion of inferior anchors being placed at the 6 o'clock position (8.3% vs. 25.0%, p=0.022) (Table 1). Rates of post-operative dislocations, recurrent instability, reoperations, all complications, and RTS also did not differ between groups (all p>0.05). Beach chair position had a trend for increase in revision rate but was not significant (beach chair 6.1% vs. lateral decubitus 1.9%, p=0.069). Finally, there was no difference between groups regarding post-operative ASES, SANE, and Oxford Shoulder Scores (all p>0.05). Conclusions: Surgical positioning for arthroscopic anterior shoulder stabilization did not affect post-operative clinical and patient-reported outcomes. Lateral decubitus patient positioning was associated with the use of fewer anchors and an increased proportion of inferior anchors placed at the 6 o'clock position of the labrum. Table 1. Comparison of intra-operative data and post-operative outcomes between patients who underwent shoulder stabilization surgery in the beach chair vs. lateral decubitus position. SLAP=superior labral tear anterior to posterior, RTS=return to sport, ASES=American Shoulder and Elbow Surgeons, SANE=Single Assessment Numeric Evaluation. Categorical data is presented as n (%), and continuous data is presented as mean ± standard deviation. Statistically significant differences are in bold.